The Politics of Sharia Economic Law in the Development of Islamic Financial Institutions in Indonesia - Reika Anggreini; Boni Sarjoni (Yayasan Darussalam Bengkulu, 2023)
Sharia economy has grown rapidly in indonesia. This is indicated by the increasing number of bank and non-bank that use sharia principles. One of the alleged supporters of this development is the political economy of sharia law conducted by the government. The problem is on the role of law politic between the sharia financial institutions regulation and the sharia financial institutions development. This research aims to privide an objective picture as well as a recommendation for the strengthening of islamic politic of law and sharia regulations. This research used normative method, which is a study on regulation, research result, journal, data and other reference, that will be analyzed by qualita tive descriptive method. The results of the study found that the politic of laws and regulations of sharia economy have contributed and established facilities for the development of islamic financial institutions in indonesia. The unity of law Politic and sharia economic regulation has established public trust and provides opportunities and protection for community, bussiness people, customers and sharia financial institutions.